PENGARUH TIME PRESSURE, AUDIT RISK, DAN LOCUS OF CONTROL TERHADAP PENGHENTIAN PREMATURE PROSEDUR AUDIT PADA BADAN PEMERIKSA KEUANGAN REPUBLIK INDONESIA PERWAKILAN SUMATERA BARAT - Denny Novi Satria; Kiki Nabilla Putri (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2022)
Premature termination of audit procedures is an event where the CPA reduces one or more audit actions required, and does not take alternatives and directly affects audit quality. The purpose of this study was to determine the effect of time pressure, audit risk, and locus of control on premature termination of audit procedures at the Supreme Audit Agency of the Republic of Indonesia, Representative of West Sumatra. The sample used is a senior or junior auditor from the Supreme Audit Agency of the Republic of Indonesia Representative of the Province of West Sumatra with a sampling technique that is purposive sampling. The analytical method used is multiple linear regression method. Based on the hypothesis, the research results simultaneously show that time pressure and audit risk have a positive effect on premature termination of audit procedures, while locus of control has a negative effect on premature termination of audit procedures. Partially, time pressure, audit risk, and locus of control have a positive effect on premature termination of audit procedures